A method of calculation of specific conductivity tensor of a anisotropic media - Kleiza, Vytautas; Kleiza, Jonas (Lietuvos matematikos rinkinys, 2005)
The article presents a method for calculating specific electrical conductivity tensor. This method is based on substantiation of uniqueness and existents theorems.